Pesticides, Microglial NOX2, and Parkinson's Disease. Issue 2 (24th January 2013) - Taetzsch, Thomas; Block, Michelle L.; Slitt, Angela L.; Hodgson, Ernest
ABSTRACT Accumulating evidence indicates that pesticide exposure is associated with an increased risk for developing Parkinson's disease (PD). Several pesticides known to damage dopaminergic (DA) neurons, such as paraquat, rotenone, lindane, and dieldrin also demonstrate the ability to activate microglia, the resident innate immune cell in the brain. While each of these environmental toxicants may impact microglia through unique mechanisms, they all appear to converge on a common final pathway of microglial activation: NADPH oxidase 2 (NOX2) activation. This review will detail the role of microglia in selective DA neurotoxicity, highlight what is currently known about the mechanism of microglial NOX2 activation in these key pesticides, and describe the importance for DA neuron survival and PD etiology. © 2013 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:137‐149, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21464